2016
DOI: 10.1111/jdv.13626
|View full text |Cite
|
Sign up to set email alerts
|

Actinic keratosis: correlation between clinical and histological classification systems

Abstract: Clinical classification of AK lesions using the system of Olsen does not accurately match histological classification of the same lesions using the system of Roewert-Huber. Consequently, it is not possible to draw conclusions about the histology of AK lesions from their clinical appearance. This finding reinforces the need to treat all AK lesions as well as field cancerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
31

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 31 publications
3
97
0
31
Order By: Relevance
“…In other words, it is not possible to predict which AKs will progress, regardless of the grade. Moreover, clinical classifications do not correlate accurately with histology . Thus, the usefulness of classifying AKs into low‐ and high‐risk lesions is questionable and should be further investigated .…”
Section: From Ak To Iscc: Is It Possible To Predict Which Aks Will Prmentioning
confidence: 99%
“…In other words, it is not possible to predict which AKs will progress, regardless of the grade. Moreover, clinical classifications do not correlate accurately with histology . Thus, the usefulness of classifying AKs into low‐ and high‐risk lesions is questionable and should be further investigated .…”
Section: From Ak To Iscc: Is It Possible To Predict Which Aks Will Prmentioning
confidence: 99%
“…From a pharmaceutical perspective, besides selectivity, also epidermal penetration and stability of the prodrug and its vehicle determine the efficacy of ALA-PDT [19].…”
Section: Photodynamic Therapy For Actinic Keratosismentioning
confidence: 99%
“…This method analyzes the extent of atypical keratinocytes (AK I-III) [18]. The two systems have recently been shown not to correlate [19]. An objective assessment of AKs for scoring their severity on the head has been developed and is described in the actinic keratosis and severity index [20].…”
mentioning
confidence: 99%
“…In the past, most AK studies excluded hyperkeratotic lesions assuming a higher risk of progression into invasive carcinoma. However, a recent study has shown that it is not possible to draw a correlation from clinical appearance to histology [7]. Furthermore, another study revealed that the thickness of AKs does not predict its dysplastic severity and thus its aggressiveness [6].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that the thickness of AK does not predict its degree of dysplasia or correlate with established histological grading systems [6, 7]. Furthermore, a lesion-based classification scheme does not adequately represent the whole area affected by AK.…”
Section: Introductionmentioning
confidence: 99%